Mercury emissions, hazards and preventive measures: A review - Abbas, T. (CRC Press/Balkema, 2015)
The impact of mercury emission on environment by natural and anthropogenic sourcesmakes the global village worried recently. In particularly, in Europe, its level of emission is quite highdue to power plants and their industrial processes. Thus, more attention is paid to it on account of itspotential hazard for workers and environment. It is vital that its level of pollution should be decreased byemission sources. The paper highlights the basic mercury sources in Europe. It also provides details abouttransportation of mercury into human body via different systems. Moreover, the associated hazards andpreventive steps are widely discussed. Finally, mercury removal technologies are presented. Â© 2015 Taylor & Francis Group, London.